Inventarisasi dan Pengelolaan Aset Tanah dan Bangunan di SMP Muhammadiyah 2 Wates yang Berkelanjutan - Dewi, Indah Kusuma; Hardin; Choirunnissa, Bustania; Asmorojati, Anom Wahyu; Jaya, Hamida Rahmad Adi (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: Land and building asset management is an important aspect in ensuring the sustainability of good school governance. This community service activity aims to improve the capacity of asset management at SMP Muhammadiyah 2 Wates through advocacy, asset certification, training in the use of information systems, and the preparation of sustainable management strategies. Method: The methods used include observation, interviews, document studies, and information technology simulations using the Muhammadiyah Asset Management Information System (SIMAM) application. Result: The results show that the school has a total land asset area of 4,500 m² with varying ownership statuses, namely certified property, uncertified property, and leased property. The existence of assets that have not been certified indicates the need to accelerate legal advocacy. In addition, SIMAM training has succeeded in increasing the understanding of school administrators regarding digital-based asset recording. This activity also produces a structured and sustainability-oriented asset management strategy, including the use of assets for educational activities and school economic development. Conclusion: This activity is expected to be a model for institutional empowerment in other schools with similar characteristics.